Multi-observatory Study of Young Stellar Energetic Flares (MORYSEF): No Evidence for Abnormally Strong Stellar Magnetic Fields after Powerful X-Ray Flares - Konstantin V. Getman; Oleg Kochukhov; Joe P. Ninan; Eric D. Feigelson; Vladimir S. Airapetian; Abygail R. Waggoner; L. Ilsedore Cleeves; Jan Forbrich; Sergio A. Dzib; Charles J. Law; Christian Rab; Daniel M. Krolikowski (The Astrophysical Journal)
We explore the empirical power-law relationship between X-ray luminosity ( L _X ) and total surface magnetic flux (Φ), established across solar magnetic elements, time- and disk-averaged emission from the Sun, older active stars, and pre-main-sequence (PMS) stars. Previous models of large PMS X-ray flares, lacking direct magnetic field measurements, showed discrepancies from this baseline law, which MHD simulations attribute to unusually strong magnetic fields during flares. To test this, we used nearly simultaneous Chandra X-ray and HET-HPF near-infrared observations of four young Orion stars, measuring surface magnetic fields during or just after powerful PMS X-ray flares. We also modeled these PMS X-ray flares, incorporating their measured magnetic field strengths. Our findings reveal magnetic field strengths at the stellar surface typical of nonflaring PMS stars, ruling out the need for abnormally strong fields during flares. Both PMS and solar flares deviate from the L _X –Φ law, with PMS flares exhibiting a more pronounced deviation, primarily due to their much larger active regions on the surface and larger flaring loop volumes above the surface compared to their solar counterparts. These deviations likely stem from the fact that powerful flares are driven by magnetic reconnection, while baseline X-ray emission may involve less efficient mechanisms like Alfvén wave heating. Our results also indicate a preference for dipolar magnetic loops in PMS flares, consistent with Zeeman–Doppler imaging of fully convective stars. This requirement for giant dipolar loops aligns with MHD predictions of strong dipoles supported by polar magnetic surface active regions in fast-rotating, fully convective stars.